(untitled) (Bioscience Journal, 2018)
The aim of this study was to conduct an inheritance study for the agronomic and chemical characteristics of basil (Ocimum basilicum L.) hybrid ’Genovese’ x ’Maria Bonita’. F1 seeds were obtained from a cross of P1 (Genovese) x P2 (Maria Bonita). F2 seeds were obtained from selfing five F1 plants. In this experiment, a randomized block design with three replications was used. Each replication consisted of four treatments (generations). Seven plants from each P1, P2 and F1 generation and 21 plants from the F2 generation were grown for each replication. The following characteristics were evaluated at full bloom: plant height, leaf dry weight, essential oil content and yield in the leaves and the main essential oil chemical constituent concentrations in each plant. The characteristics plant height, essential oil yield and linalool content are controlled by more than one major gene, and these genes present additive and dominant effects. High heritability was observed for the characteristics plant height, leaf dry weight and content of linalool and 1,8-cineole. The hybrid ’Genovese’ x ’Maria Bonita’ presented a plant height and dry leaf weight heterosis of 32.31% and 131.54%, respectively.